Single-cell analysis of Mycobacterium tuberculosis with diverse drug resistance using surface-enhanced Raman spectroscopy (SERS) - Andrey Zyubin; Anastasia Lavrova; Marine Dogonadze; Evgenii Borisov; Eugene B. Postnikov (PeerJ)
In this work, we investigated individual bacteria M. tuberculosis belonging to strains of the Beijing family with different drug sensitivity (sensitive, multi and extensive drug-resistant) by surface-enhanced Raman spectroscopy (SERS) in the fingerprint region. The latter is focused on the spectral bands, which correspond to a set of glutathione bands and DNA methylation patterns revealed due to 5-methylcytosine spectral biomarkers. It is shown that these spectral features can be correlated with drug sensitivity and DNA methylation. Thus, since this kind of diagnostics is fast and operates with individual cells, it can be considered a promising tool, which significantly shortens the time required for a strain’s type identification necessary to prescribe adequate therapy.